Katolicka nauka społeczna a religijność seniorów w czasie pandemii Covid-19 - Bolesław Karcz (Edukacja Ustawiczna Dorosłych)
The Church has been seeking spiritual and material help for the poor, the lost and the elderly from the very beginning of its existence. It has been expressed, on the one hand, in living one's faith by taking up religious practices, and on the other hand, it has been a concern for various social groups, including seniors, for whom social engagement opportunities were organized. Institutional external forms such as Lazarets have also been built. The article is a preliminary analysis of this topic, as we are still struggling with the virus pandemic. Nevertheless, various actions have been taken by the Church based on Catholic social teaching, and these are set out in this article.